The Influence of the Policy of the Head of the Education Unit on the Implementation of the Healthy School Movement and the Improvement of Healthy Lifestyles of SD Negeri 018 Purnama Students - Suprihatina, Eka Sri (Journal of English Language and Education, 2025)
This study aims to determine the effect of the principal’s policy on the implementation of the Healthy School Movement (HSM) and the improvement of students’ healthy lifestyle at SD Negeri 018 Purnama. The research used a descriptive quantitative method with a sample of 30 fifth-grade students. Data were collected through questionnaires and documentation, and analyzed using regression tests. The results showed that the principal’s policy had a positive and significant effect on the implementation of the HSM in the nutritious and healthy aspects and Clean and Healthy Living Behavior (CHLB). The contribution of the independent variables to the dependent variable reached 69%. Therefore, it can be concluded that the principal’s policy plays an important role in the success of the HSM program in elementary schools.